PERSON DEIXIS IN NARRATIVE (ON THE MATERIALS OF RUSSIAN AND MACEDONIAN TALES) (Philological Studies, 2019)
The objective of this work is an attempt to show the features of personal deixis in narrative on the materials of the Macedonian and Russian folk texts. In article is considered the specifics of the means for expressing personal deixis in narrative, their similarities and differences in both languages are examined.
Keywords: Russian language, Macedonian language, personal deixis, the pronoun I, means of expression, narrative, secondary deixis, folklore texts